PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA BENGKEL SISAM PEMATANGSIANTAR - Ananda, Risky; Lie, Darwin; Butarbutar, Marisi; Inrawan, Ady (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2018)
The purpose of research is: 1. Description of product quality, service quality, customer loyalty and customer satisfaction on Lathe Workshop Sisam Pematangsiantar. 2. The influence of product quality and service quality againts customer satisfaction on Lathe Workshop Sisam Pematangsiantar simultaneously. 3. The influence of product quality and service quality againts customer satisfaction on Lathe Workshop Sisam Pematangsiantar partially. 4. The influence customer satisfaction againts customer loyalty on Lathe Workshop Sisam Pematangsiantar. Design research is the research library and field research. The data type used is qualitative and quantitative and data. Data sources are primary data and secondary data. The population in this research is the customer Lathe Workshop Sisam Pematangsiantar of 40 people. Data collection is done with the interview, questionnaire and the documentation. Analytical techniques used was multiple linier regression analysis and simple, correlation coefficient, coefficient of determination, and hypothesis testing.Research result can be summed up as follows: 1. Description of product quality are very well,Â well service quality, customer satisfactionÂ satisfied and customer loyalty well. There is a positive influence between product quality and service quality toward customer satisfaction evidenced by the regression Å¶ = 3,781 + 0,180 X1 + 0,256 X2. 2. There is a positive influence between customer satisfaction toward customer loyalty evidenced by the regression Å¶ = 5,987 + 1,157 X 3. There is moderately high and positive correlation between product quality and service quality with customer satisfaction evidenced by r = 0,821 and R Square = 0,674. There is high and positive correlation between customer satisfaction with customer loyalty is evidenced by the r = 0,816 and R Square = 0,670. 4. The results of the hypothesis H0 is rejected, meaning that product quality and service quality a positive and significant effect against the customer loyalty with the customer satisfaction simultaneously intervening variables as well as partial.Â Keyword: product quality, service quality, customer satisfaction and customer loyalty.